SPE Asia Pacific Oil and Gas Conference and Exhibition 2000
DOI: 10.2118/64398-ms
|View full text |Cite
|
Sign up to set email alerts
|

Screen Selection for Sand Control Based on Laboratory Tests

Abstract: Oil and gas production from unconsolidated/weakly-consolidated sands requires a production screen in the hole to inhibit the movement of formation sand and keep the hole open. For open hole completions where the sand control screen directly retains the formation sand, proper screen selection is necessary to provide optimum life and minimum sand passing. Several screen sizing selection criteria are available in the literature such as Saucier, Coberly, Schwartz and others. However, these rules may not always be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2002
2002
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…Gillepse et al 9 suggested the use of different types of screen technology based on the uniformity coefficient, and the size and variation of d50 of the formation sand. Direct retention SAS is not effective when the sand is highly non-uniform, and/or there is too much variability in reservoir sand sizes.…”
Section: Screen Sizingmentioning
confidence: 99%
See 1 more Smart Citation
“…Gillepse et al 9 suggested the use of different types of screen technology based on the uniformity coefficient, and the size and variation of d50 of the formation sand. Direct retention SAS is not effective when the sand is highly non-uniform, and/or there is too much variability in reservoir sand sizes.…”
Section: Screen Sizingmentioning
confidence: 99%
“…Gillepse et al proposed that; for premium screens, screen opening could be up to 2.5 times the d50 sand size, while for wire wrap screens, the slot width should not exceed twice the d50 of sand size. Refer to Figure 2: Criteria for Premium (Mesh Screen) Sizing [SPE-64398] 9 . However, it should be emphasized that historical knowledge and experience of the field shall supersede this recommendation; if SAS of other size has been run in this sand in other wells and have provided favourable results over the years.…”
Section: Screen Sizingmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Guidelines for screen selection, performance evaluations of the screens, laboratory testing procedures, and the design of drilling and completion fluids could be found in the cited references.…”
Section: Experimental Studies and Field Applicationsmentioning
confidence: 99%
“…Sizing of sand-control media for oilfi eld applications has been the subject of many laboratory studies dating back to the early 1900s (Coberly 1937;Suman et al 1985;Markestad et al 1996;Tiffi n et al 1998;Malbrel et al 1999;Ballard et al 1999;Underdown et al 1999;Gillespie et al 2000;Hodge et al 2002;Ballard and Beare 2003;Constien and Skidmore 2006;Williams et al 2006;Ballard and Beare 2006;Mathisen et al 2007;Underdown and Hopkins 2008). Chanpura et al (2010) provide a thorough review of the past work on screen selection for SAS applications.…”
Section: Introductionmentioning
confidence: 99%